The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Oxford Handbooks Online 2017
DOI: 10.1093/oxfordhb/9780190464684.013.21
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Shaping of Compassion

Abstract: In this chapter, we first review the existing literature on cross-cultural studies on compassion. While cultural similarities exist, we demonstrate cultural differences in the conception, experience, and expression of compassion. Then we present our own work on the cultural shaping of compassion by introducing Affect Valuation Theory (e.g., Tsai, Knutson, & Fung, 2006), our theoretical framework. We show how the desire to avoid feeling negative partly explains cultural differences in conceptualizations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Healthcare research has examined compassion from the perspective of: the predictors of compassion in healthcare professionals ( Fernando and Consedine, 2014 ; Bleiker et al, 2020 ; Pavlova et al, 2022 ); how care environment and organizational culture affect compassion ( Casagrande, 2016 ; Ali and Terry, 2017 ; Dev et al, 2019 ; Tehranineshat et al, 2019 ; Wiljer et al, 2019 ; Ali et al, 2022 ); compassion-maintaining strategies and interventions ( Blomberg et al, 2016 ; Terry et al, 2017 ; Flores and Brown, 2018 ; Baguley et al, 2020 ; Hopkins et al, 2021 ; Malenfant et al, 2022 ); compassionate leadership ( Dewar and Cook, 2014 ; de Zulueta, 2015 ; Lown et al, 2019 ; West et al, 2020 ); and regulation of compassionate caregiving ( Harris et al, 2019 ; Pedersen and Roelsgaard Obling, 2019 ). Culturally and critically informed perspectives of compassion highlight that different societies, professional groups, cultures, and generations hold different expectations and views about compassion ( Koopmann-Holm and Tsai, 2017 ; Sundus et al, 2020 ) which change over time ( Salvador Zaragozá et al, 2021 ). Compassion has been described as a lens for critically considering the cultural and social significance of AI technologies and the different ways that such technologies may serve or disserve the societies that created them ( White and Katsuno, 2019 ) including how technologies affect their users ( Day et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare research has examined compassion from the perspective of: the predictors of compassion in healthcare professionals ( Fernando and Consedine, 2014 ; Bleiker et al, 2020 ; Pavlova et al, 2022 ); how care environment and organizational culture affect compassion ( Casagrande, 2016 ; Ali and Terry, 2017 ; Dev et al, 2019 ; Tehranineshat et al, 2019 ; Wiljer et al, 2019 ; Ali et al, 2022 ); compassion-maintaining strategies and interventions ( Blomberg et al, 2016 ; Terry et al, 2017 ; Flores and Brown, 2018 ; Baguley et al, 2020 ; Hopkins et al, 2021 ; Malenfant et al, 2022 ); compassionate leadership ( Dewar and Cook, 2014 ; de Zulueta, 2015 ; Lown et al, 2019 ; West et al, 2020 ); and regulation of compassionate caregiving ( Harris et al, 2019 ; Pedersen and Roelsgaard Obling, 2019 ). Culturally and critically informed perspectives of compassion highlight that different societies, professional groups, cultures, and generations hold different expectations and views about compassion ( Koopmann-Holm and Tsai, 2017 ; Sundus et al, 2020 ) which change over time ( Salvador Zaragozá et al, 2021 ). Compassion has been described as a lens for critically considering the cultural and social significance of AI technologies and the different ways that such technologies may serve or disserve the societies that created them ( White and Katsuno, 2019 ) including how technologies affect their users ( Day et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies demonstrate that meditation practices increase compassion, no studies were found that examine whether these findings are maintained across different ethnic and cultural groups. In fact, researchers are finding that some cultural differences exist in the conception, experience, and expression of compassion, which may have implications for how counselors may interpret and integrate the practices into their lives (Koopmann‐Holm & Tsai, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Compassion can be conceptualized as a connected triad (Gilbert, 2009b), with compassion being from others, toward others, and/or toward oneself (i.e., self-compassion). Although compassion is shaped to some extent by culture (e.g., individualistic vs. more collectivist cultures; Koopmann-Holm & Tsai, 2017), a number of core elements can be found across cultures. Strauss and colleagues (2016) described compassion as “awareness of someone’s suffering, being moved by it…, and acting or feeling motivated to help” (pp.…”
Section: Role Of Compassion In Suicide Preventionmentioning
confidence: 99%